A task-resource dependency perspective on partner selection during the formation of networked business constellations. (1st September 2010) - Zarvic, Novica; Seifert, Marcus; Thoben, K-D.
The organisational forms of networked business constellations in general are often interpreted as the new organisational forms of the 21st century. As far as such forms consist of multiple collaborating businesses, partner selection during the formation phase of a networked business constellation is a crucial task for successful operation in the future. We propose to choose the appropriate business partners by applying concepts from coordination theory. In particular, we decompose an identified business opportunity, usually an innovative product or service, into its embracing tasks and resources. These represent the competencies needed for meeting the business opportunity. The methodological approach for partner selection is discussed from a task-resource dependency perspective and the benefits for the networked business context are highlighted. The research in this paper is accompanied by an argumentation-based validation, as well as by an evaluation of sustainability.